An introduction to the Unitarian and Universalist traditions - Greenwood, Andrea, 1961-; Harris, Mark W. (New York : Cambridge University Press, 2011)
"How is a free faith expressed, organised and governed? How are diverse spiritualities and theologies made compatible? What might a religion based in reason and democracy offer today's world? This book will help the reader to understand the contemporary liberal religion of Unitarian Universalism in a historical and global context. Andrea Greenwood and Mark W. Harris challenge the view that the Unitarianism of New England is indigenous and the point from which the religion spread. Relationships between Polish radicals and the English Dissenters existed and the English radicals profoundly influenced the Unitarianism of the nascent United States. Greenwood and Harris also explore the US identity as Unitarian Universalist since a 1961 merger and its current relationship to international congregations, particularly in the context of twentieth-century expansion into Asia"--
Machine generated contents note: 1. Liberal religion and the foundations of the Unitarian and Universalist faiths; 2. The European background; 3. Great Britain; 4. Early America; 5. Unitarians and Universalists in the Republic; 6. A religion for one world; 7. Polity; 8. Theology; 9. Worship; 10. Science and ecology; 11. Architecture, music and the arts; 12. Education, welfare and human rights; 13. Unitarian Universalism in the 21st century.
Includes bibliographical references and index.
Keywords: Unitarian Universalist churches -- Doctrines